Inclusive access to seed: Catalyzing sectoral synergies and tracking change - Tenneti, Suchaita; Puskur, Ranjitha; Pandia, Gyandip; Khan, Afreen (International Rice Research Institute, 2024)
Varied definitions and interpretations of formal and informal seed systems and what constitutes these two sectors pose a challenge for any discussion on seed system synergies. To facilitate discussions, the participants agreed that any class of seed that is developed by research institutions and is governed by the legal infrastructure of the state would be considered the formal sector. Currently, certified seed and all the mechanisms of certified seed production are included within the formal sector. Informal seed systems are entirely farmer-managed and include various classes of seeds that are either partially or not at all controlled by legal mechanisms. Certain seed classes such as Truthfully Labeled (TL) seeds can be regarded as an intermediate category that could fall under either the formal or the informal sector as they are subjected to some regulatory frameworks but not to the extent that certified seeds are.